Empowering Geduang Village community through the establishment of a waste bank - Laili Qomariyah; Muhammad Dzikki Annawaf; Lutfiani Lutfiani; Nanda Ristina; Yulia Nisvi Aryani; Aldi Dwi Pamungkas (Community Empowerment, 2022)
Until now, the waste management in Geduang Hamlet has not been optimal, even though waste can be processed into goods of economic value. Limited knowledge and lack of skills are obstacles in waste management. Therefore, efforts are needed to improve human resources in the management of organic and inorganic waste. Community empowerment through the formation and management of waste aims to provide education to the public about the Waste Bank starting from the establishment to the administrative mechanism. This program is carried out in the form of training. The results obtained from this program are that the waste bank management has been able to formulate a vision and mission, understand an efficient waste sorting process, and increase the solidity of managers and more organized financial planning management.